A comparative study on the effect of propolis and dentine bonding agent in treating dentine hypersensitivity - Ather Akber; Shahbaz Ahmed; Syed Muhammad Umer Hasan; Admin (Journal of the Pakistan Medical Association, 2022)
Objective: To find out if there is a difference in the efficacy of propolis and seventh-generation dentine bonding agent in reducing dentine hypersensitivity. Method: The randomised, single-blind study was conducted at the Department of Periodontology, Dow International Dental College, Dow University of Health Sciences, Karachi, from December 2018 to November 2019, and comprised patients with complaint of dentine hypersensitivity who were divided in group A which received 30% ethanolic extract of propolis, and group B which received dentine bonding agent. Recordings of dentine hypersensitivity were obtained at baseline, before and after the application of experimental agents, and on days 7, 15 and 30. The response was measured using the Schiff Cold Air Sensitivity Scale. Data was analysed using SPSS 20. Results: Of the 52 patients, 19 (36.5%) were males and 33 (63.5%) were females. The overall mean age was 29.9 ± 6.5 years. Majority of the subjects were students i.e. 16 (30.8%) and housewives i.e. 11 (21.2%), while drivers, teachers, businessmen etc. constituted of 25 subjects (48%). Significant reduction of dentine hypersensitivity was observed in both groups (p<0.05). Intergroup comparison showed non-significant differences (p>0.05). Conclusion: Propolis and dentine bonding agent had significant effect in reducing dentine hypersensitivity. The difference between the two was not significant. Key Words: Dentine hypersensitivity, DH, Propolis, Dentine bonding agent, Schiff cold air sensitivity scale.